Deposition of mullite in peatlands of southern Poland: Implications for recording large-scale industrial processes. (July 2019) - Smieja-Król, Beata; Fiałkiewicz-Kozieł, Barbara; Michalska, Anna; Krzykawski, Tomasz; Smołka-Danielowska, Danuta
Abstract: Mullite, a pure aluminosilicate (Al6 Si2 O13 ), is a rare natural rock component, known for centuries as a very resistant ceramic material. It is also a common waste product of high-temperature coal combustion that is emitted in quantity from coal-based power stations. The occurrence of mullite in two S phagnum -dominated peatlands located near the Upper Silesia industrial region in southern Poland is described. For the first time, a complete record of mullite deposition in the peat profiles has been obtained by XRD analyses of ashed peat samples. The mullite distribution is compared with records of Hg, Pb and Cu. While mullite is supplied during high temperature processes only, Cu, Pb and Hg show more complex pattern of distribution. Both peat profiles contain elevated amounts of mullite in the time span between ca 1950–1990 with a maximum content in ca 1980. The first appearance (∼1900) of mullite is indicative of the beginning of energy production in coal-based power plants in the region. Mullite is proposed here as an indicator of industrialization in geological records. It is resistant to post-depositional processes, emitted globally, and restricted to large-scale industry. Graphical abstract: Image 1 Highlights: Mullite, a weathering-resistant phase, is emitted in quantity from coal-based power stations as a component of fly ash. Decades of mullite deposition was recorded in peat profiles for the first time. The first appearance of mullite in peat is indicative of the beginning of energy production in coal-based power plants. Mullite has a great potential to be used as an indicator of industrialization in geological records. Abstract : Not all contaminants are harmful, mullite has the potential to be useful.